Surface based morphometry in Alzheimer's disease - Uluğ, Esma Ece. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
Alzheimer’s disease( AD) is aneurodegenerativedisorderespeciallyaﬀectingthe elderlypopulationwhichisgrowingworldwide. Inthisstudy, surface-basedmorphometry analysis was performed on anatomical MR images of patients with Alzheimer’s Disease (AD) and healthy control (HC) subjects using a computational anatomy toolbox called CAT(Computational Anatomy Toolbox) on SPM (Statistical Parameter Mapping) platform. MR images were obtained from a database named Minimal Interval Resonance Imaging in Alzheimer’s Disease (MIRIAD) consisting of 46 AD patients and 23 HC subjects. The cortical thickness measurements were performed over 34 different regions on each hemisphere deﬁned by Desikan-Killiany anatomical atlas. The t-statistics parameters of the cortical thickness values were found to be decreased in 24 regions in AD patients compared with the HC subjects. Additionally, the linear correlation values between the MMSE scores and cortical thickness values of AD and HC individuals were estimated for each atlas region. Accordingly, 28 regions exhibited a signiﬁcant correlation between MMSE(Mini Mental State Examination) scores and cortical thickness values. Signiﬁcant regions that were aﬀected by AD were observed to be as parietal, temporal, frontal, cingulate and occipital lobes as reported in previous studies.|Keywords : Alzheimer’s Disease, Magnetic Resonans Imaging, Surface Based Morphometry, Cortical Thickness, Computational Anatomy Toolbox, Desikan-Killiany Atlas, Mini Mental State Examination.
Keywords: Alzheimer's disease.